1988
DOI: 10.1128/iai.56.6.1526-1531.1988
|View full text |Cite
|
Sign up to set email alerts
|

Immunization of cattle with a 36-kilodalton surface protein induces protection against homologous and heterologous Anaplasma marginale challenge

Abstract: Immunization of cattle with a purified Anaplasma marginale major surface protein, AmF36, induced protection against homologous challenge with the Florida isolate. Similarly, immunized cattle were protected from challenge with the antigenically and structurally distinct Washington-O isolate of A. marginale. The degree of protection in AmF36-immunized cattle varied from complete prevention of rickettsemia to significant delay in the onset of rickettsemia compared with control immunized cattle. A single AmF36 vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(36 citation statements)
references
References 19 publications
0
33
0
Order By: Relevance
“…In addition, an A. marginale membrane fraction can induce protective immunity against rickettsemia and anemia that correlates with anti-MSP antibody titers (31). However, immunization with isolated MSPs has induced only partial protection against challenge (20,21,24). One explanation for these data is that immune responses to epitopes on multiple MSPs are required for protective immunity.…”
Section: Msp Complexes (I) Solubilized Wholementioning
confidence: 99%
See 2 more Smart Citations
“…In addition, an A. marginale membrane fraction can induce protective immunity against rickettsemia and anemia that correlates with anti-MSP antibody titers (31). However, immunization with isolated MSPs has induced only partial protection against challenge (20,21,24). One explanation for these data is that immune responses to epitopes on multiple MSPs are required for protective immunity.…”
Section: Msp Complexes (I) Solubilized Wholementioning
confidence: 99%
“…Sera from these protected cattle recog-nize MSP-1, MSP-2, MSP-4, and MSP-5, and antibody titers against the MSPs correlate with protection against anemia (31). In contrast to the protection induced by immunization with outer membranes, vaccination with isolated MSPs induces incomplete protection (20,21,24). In this context, we hypothesized that the intermolecular relationships of MSPs are important for induction of complete protective immunity and initiated the analysis reported here.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…The immune response to the A. marginale surface is directed predominantly to a subset of outer membrane proteins, including major surface protein 2 (MSP2), which is an immunodominant 36 -44 kDa protein that has highly conserved amino and carboxy regions flanking a central hypervariable region (HVR) [3,[7][8][9]. Conserved regions and HVR of MSP2 contain numerous major histocompatibility complex (MHC) class II-restricted CD4 ϩ T cell epitopes, consistent with the immunodominant nature of this surface protein [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…We have proposed that each cycle of persistent rickettsemia reflects emergence of antigenically variant A. marginale that are subsequently controlled by variant-specific primary immune responses (6,21). Our studies have focused on the A. marginale major surface protein 2 (MSP2), an immunodominant outer membrane protein (6,12,16,17,26). MSP2 is encoded by a large, polymorphic, multigene family that provides the genetic capacity for variation (3,16), and we have shown that transcripts encoding unique, polymorphic MSP2 proteins are expressed in sequential rickettsemic cycles (6,21).…”
mentioning
confidence: 99%